An alternate method of fabrication of an obturator in a patient diagnosed with melanotic neuroectodermal tumor of infancy - Kanchan P Dholam; Gurkaran Preet Singh; Sandeep V Gurav; Arati A Shinde (Indian Journal of Medical and Paediatric Oncology)
The quality of treatment and rehabilitation for the pediatric head and neck cancer patient has greatly improved due to interdisciplinary management. Surgical resection of maxilla leads to functional impairment which can be adequately restored with an obturator. However, its fabrication can be challenging in a pediatric patient. A simple, practical, and time-saving procedural modification in the fabrication of obturator in a patient diagnosed with rare melanotic neuroectodermal tumor of infancy has been presented.